Stressors of NICU mothers and the effect of counseling—experience from a tertiary care teaching hospital, India. (April 2013) - Chourasia, Nitish; Surianarayanan, Pushkala; Bethou, Adhisivam; Bhat, Vishnu
<x xml:space="preserve">Abstract</x> Objective: To determine the effect of counseling on stress levels of NICU mothers. Methods: Stress levels were assessed using the Parental Stressor Scale: Neonatal Intensive Care Unit (PSS:NICU) questionnaire among 100 NICU mothers. After providing counseling including NICU educational support, the questionnaire was re-administered after 48 h. Coding of the responses was done and the data was analyzed using SPSS Ver.16. Results: The mean pre intervention subscale stress score was highest for parental role alteration (4.12) followed by looks and behavior of the baby (4.10) and sights and sounds (2.55). There was significant reduction in the post-counseling stress levels among NICU mothers in all three sub scales of PSS:NICU. Conclusion: Counseling of mothers whose babies are admitted to the NICU with regards to various aspects of the infant`s environment and condition was significantly effective in reducing the stress levels of mothers.